Green Branding and its Effects on Consumer Attitudes An Empirical Study using the Example of Sustainable Coffee - Haefke, Juliane (2012)
Purpose – The objective of this study was to review existing research on environmentally friendly marketing and to gain a more profound understanding of green branding as one possible marketing tool to positively influence consumers’ attitudes. In this respect, different types of green brand messages were assessed against each other and their effects on consumers’ attitudes and purchase intentions were tested.